Successful endothelialization and remodeling of a cell-free small-diameter arterial graft in a large animal model. (January 2016) - Koobatian, Maxwell T.; Row, Sindhu; Smith Jr, Randall J.; Koenigsknecht, Carmon; Andreadis, Stelios T.; Swartz, Daniel D.
Abstract: The large number of coronary artery bypass procedures necessitates development of off-the-shelf vascular grafts that do not require cell or tissue harvest from patients. However, immediate thrombus formation after implantation due to the absence of a healthy endothelium is very likely. Here we present the successful development of an acellular tissue engineered vessel (A-TEV) based on small intestinal submucosa that was functionalized sequentially with heparin and VEGF. A-TEVs were implanted into the carotid artery of an ovine model demonstrating high patency rates and significant host cell infiltration as early as one week post-implantation. At one month, a confluent and functional endothelium was present and the vascular wall showed significant infiltration of host smooth muscle cells exhibiting vascular contractility in response to vaso-agonists. After three months, the endothelium aligned in the direction of flow and the medial layer comprised of circumferentially aligned smooth muscle cells. A-TEVs demonstrated high elastin and collagen content as well as impressive mechanical properties and vascular contractility comparable to native arteries. This is the first demonstration of successful endothelialization, remodeling, and development of vascular function of a cell-free vascular graft that was implanted in the arterial circulation of a pre-clinical animal model.